Geoensine: Uma proposta de curadoria de conteúdos digitais e formação colaborativa de professores de geografia - Almeida, Daniela Gomes de (2023)
This study was developed in a context in which the internet and cyberspace become inseparable components of geographic space. This combination results in a complex socio-spatial scenario that has profound impacts on people's everyday lives. Such transformations not only affect the educational environment and the teaching of Geography, but also promote discussions and significant changes in teacher education. Using qualitative research processes with an applied approach and employing multiple methods of data collection, such as questionnaires, participant observation and the creation of digital environments, ways to strengthen the collaborative training of Geography teachers were explored through an online and transmedia perspective. The main objective of this study was to investigate how to facilitate the exchange of experiences, teaching materials and theoretical knowledge, carrying out this exchange through the creation and curation of digital content and teaching collaboration in a network. To achieve this purpose, the training needs of a group of Geography teachers were investigated and, based on the collected data, the GeoEnsine project was developed on digital platforms, such as the social network Instagram and the already consolidated Observatório de Ensino de História e Geografia. Through participant observation in a digital environment and applying knowledge about the configuration of online content, collaborative interfaces were built to enjoy the transmedia convergence between platforms. As a result of this approach, it was possible to structure a way of creating a networked teacher education system, enabling educators to share, collaborate and co-create enriching educational experiences. By interacting in digital environments, it was possible to disseminate, curate content, collaborate in the creation and re-creation of experiences, culminating in a meaningful formative process. In this sense, the research demonstrated that the curation of digital content in education is an important practice amidst the intense profusion of artifacts and information that circulate on the internet. In this environment, it is necessary to choose, select and recommend those that are most meaningful and appropriate for the pedagogical work. Furthermore, the curator activity becomes even more relevant when it involves the collective participation of teachers and the sharing of experiences, materials and trajectories in the teacher education process.